DAYA MENGIKAT AIR DAN SUSUT MASAK DAGING SAPI BLANSIR YANG DIKERINGKAN DALAM OVEN DAN DIKEMAS VAKUM - Rompis, John E. G. (Universitas Sam Ratulangi, 2015)
WATER HOLDING CAPACITY AND COOKING LOSS OF DRIED AND VACUUM PACKAGE BEEF MEAT. Fresh meat is categorized into perishable physical and chemical material product due to high nutrient composition as the main media of growing microorganism. This meat damage could be handled by drying and vacuum package method. The objective of this study was to evaluate effect of drying time period and storage time period on water holding capacity and cooking loss of vacuum package beef meat. Treatment was conducted using completely randomized design divided into two factors with three replications in each combination of the factors. Factor A, as main plot of drying time period was divided into 12 hours (A1), 16 hours (A2) and 20 hours (A3). Factor B as sub plot of storage time period in room temperature of 270 C was divided into 00 C (B0), 120 C (B1), 240 C (B2), and 360 C (B3). Results showed that treatments affected significantly quality of beef meat. There was no interaction effect on water holding capacity and cooking loss of vacuum package beef meat. Beef meat being dried during 16 hours with temperature of 60 0C using vacuum package and stored at room temperature of 270 C during 36 days produced normal standard of water holding capacity and cooking loss of meat. Â Key words: water-holding capacity, cooking loss, vacuum package.